Sustainable development goals as a perspective for higher education institutions - Geryk, Marcin (Research Papers of Wrocław University of Economics, 2018)
Universities are now faced with a huge challenge. They need to see the changein society and due to this, they must change themselves. United Nations EnvironmentProgramme might be helpful in this process. The implementation process is difficult as manypeople are involved. The understanding of the process and of its necessity must be shared byevery member of a particular institution. The term ‘sustainable development’, even if used socommonly, may be understood differently, so further research is suggested on clarifying theterm. Due to its popularity, many universities are now involved in many activities like signinga declaration of sustainable development or other initiatives. For some of those institutions, itis an apparent action that is not followed by any action later. The goals itself are very usefulfor higher education institutions as they play a role of a road map on the way to establishingstrong and living links with the society as such, represented by stakeholders
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2018; Nr 520; s. 54-63
Keywords: sustainable development; uniwersytety; perspektywa; przyszłość; szkolnictwo wyższe